Strategi Guru Pendidikan Agama Kristen Dalam Membangun Lingkungan Belajar Yang Kondusif - Melyar Mes; Gusti Sette; Rianto Metboki; Levi Lefta (Institut Agama Kristen Negeri Kupang, 2022)
The basic problem of this article is the idea that the learning strategies of Christian religious education teachers must be improved. The problem that often arises is the lack of motivation for PAK teachers to learn to increase professionalism in implementing Christian religion learning strategies according to the needs and conditions of students in class. The purpose of this research is that PAK teachers can carry out learning with strategies that have a positive effect on the development of a fun learning environment and have a good impact on students' personalities in navigating the values of Christian religious education for life. In this study, the authors used a qualitative method with a literature study approach. The research results obtained several principles of building a conducive learning environment, namely: structuring study rooms, teaching and learning atmosphere, communication and social relations, being a fun PAK teacher, letting students be creative, agreeing on rules together to create a conducive learning atmosphere so that students succeed in learning.